Campanelli and Paradise vs. Italy case before the European Court of Human Rights: family de facto concept and its contribution to the surrogacy) - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In 2017, the Grand Chamber of the European Court of Human Rights (ECHR) rendered its second ruling with regard to the case Paradiso and Campanelly vs. Italy, two years after the first ruling was rendered in 2015. This contribution is aimed to highlight the most remarkable statements of this second Judgment taking into account that this case was never considered a case of surrogacy as such. The moot point relies on the scope and implementation of the Article 8 of the Convention on the Protection of Human Rights and Fundamental Freedoms and the assessment of a real familiar de facto bond in cross border surrogacy cases, given by the judges in this judgment.
Keywords: Article 8 CPHFR; best interest of the child; family bonds; family life de facto; right to respect the private life; State interference; public policy; surrogacy